A compact half‐mode substrate integrated waveguide bandpass filter based on highly confined slow waves with loading capacitive patches - Ning‐Ning Wang; De‐Wei Zhang; Qing Liu; Hang Qian; Wei‐Zhe Qu (IET Microwaves, Antennas & Propagation)
Abstract A novel slow‐wave half‐mode substrate integrated waveguide (HMSIW) bandpass filter (BPF) is proposed based on spoof surface plasmon polaritons (SSPPs) with loading capacitive patches (LCPs). The bandpass characteristics are achieved by etching complementary SSPPs on the metal patches of the HMSIW. SSPPs exhibit a slow‐wave effect, which effectively reduces the overall size of the filter. At the same time, using proper LCPs between the HMSIW metal via and the complementary SSPPs structure, the effective dielectric constant of the HMSIW can be changed, reducing the low cutoff frequency and further facilitating the miniaturisation of size. A prototype of the proposed filter is designed, fabricated, and measured. The measured results show that the proposed filter has the in‐band insertion loss of 1 and 3 dB passband range of 6.4–9.8 GHz.